The Cognitive Picture of Samogitian in Lithuanian and Polish - Rutkovska, Kristina; Bogdzevič, Monika (Slavistica Vilnensis, 2017)
In this paper, an attempt is made to reveal the cognitive picture of Samogitian in Lithuanian and Polish. The linguistic–cultural picture of Samogitian, encoded in Lithuanian and Polish dictionaries and other written sources, is being reconstructed both from historical and contemporary perspectives. The authors aim to find answers to the question whether there are more similarities or differences of vision of this Lithuanian ethnic group in two different cultural–linguistic layers. In order to present the most thorough understanding of how Samogitian is entrenched in language and culture, an analysis is made with the application of the Polish ethnolinguistic methodology, presented by prof. Jerzy Bartmiński. Resources used in this research include lexicographical and textual sources as well as data collected in the survey.The analysis shows that there are lots of similarities between the Lithuanian and Polish visions of Samogitian. Hence, there is no reason to maintain that these two linguistic traditions represent distinct points of view or different profiles of the concept. There is an historical evidence supporting this statement. Polish sources reveal the vision of Samogitian and Samogitia as closely related to Poland. Samogitian is being perceived in it as honorable, full of patriotism, courtly ethos and loyalty to national traditions. Wefts of courtly ethos and loyalty to the nation culture and traditions are also found in Lithuanian sources; still, here they are a good starting point for a further discussion on historical, cultural, ideological and even biological determinants of a Samogitian’s character and identity. Lithuanian sources emphasize the viability of the concept, the intricacy of the vision of Samogitian, it’s transformations and ethnic consciousness, which are still alive. NATIONALITY and CHARACTER FEATURES constitute the core underlying structure upon which the cognitive picture of Samogitian is based. The development of the concept is hidden in contemporary realities, determined by a Samogitian’s everyday life and relations with the representatives of other Lithuanian ethnic groups.
Keywords: Samogitia; Samogitian; ethnolinguistics; concept; cognitive picture